Dynamic multicast link selections for buffer‐aided relaying networks. (6th May 2016) - Chiti, Francesco; Fantacci, Romano; Pierucci, Laura
Summary: The management of small cell is considered a key point in next‐generation cellular networks for providing higher data rates, and the relay nodes are expected to be useful to improve the coverage area. Moreover, multicast services have gained importance to disseminate common data to subscribers. The use of buffer‐aided relay for multicast communications is analysed in the paper, and different policies to perform the optimal link selections are compared. These policies are based on the knowledge of the instantaneous link quality indicators as well as the status of the relay buffer and dynamically select the better link according to a suitable probabilistic criterion by improving the aggregate multicast flows. The parameters of these multicast policies are optimized via a Markov chain theoretical framework. The performance for all the proposed methods is analytically derived and validated through computer simulations conducted in different multicast scenarios. The advantages of the proposed schemes are pointed out in terms of multicast throughput, buffer occupancy for different buffer and multicast group size. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : The use of relay nodes in next‐generation cellular networks is considered a key point for providing higher data rates and broadening the coverage area. At the same time, multicast services have nowadays gained importance to disseminate data to a set of subscribers. This paper investigates the use of buffer‐aided relay for multicast communications. Different optimization policies are presented in order to improve the system performance and lower the power consumption. Performance comparisons with alternative schemes are also provided in the paper in order to highlight the advantages of the proposed methodologies.